ANALISIS LITERATUR REVIEW: PENGARUH MODEL INQUIRY LEARNING TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Zahwa, Kanaya; Darman, Dina Rahmi; Edwita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Inquiry Learning model on students’ learning motivation in IPAS instruction at the elementary school level. The study employed a qualitative approach using the Systematic Literature Review (SLR) method, analyzing 15 scientific journal articles published between 2021 and 2026. Data collection was carried out using the documentation technique by selecting articles based on inclusion and exclusion criteria related to the Inquiry model, learning motivation, and IPAS learning in elementary schools. The results of the study indicate that the implementation of Inquiry Learning has a positive effect on increasing students’ learning motivation, particularly in IPAS lessons in elementary schools. Students become more active, enthusiastic, and highly curious, and are directly involved in the learning process through investigative activities, observation, experimentation, and problem-solving. Additionally, the use of supporting media such as videos, interactive media, and digital simulations helps strengthen students’ learning motivation. However, several challenges were identified in its implementation, such as time management, teacher readiness, and differences in student characteristics. The Inquiry Learning model can serve as an effective alternative approach to enhance student motivation in IPAS learning at the elementary school level. Keywords: Inquiry-Based Learning Model, student motivation, Natural and Social Sciences, Elementary School